Intervensi Pemerintah terhadap Pajak dan Retribusi Daerah dalam Rangka Proyek Strategis Nasional - Herwin, Andi Deni; Hutagaol, Henry D. (Amsir Law Journal, 2023)
Indonesia is a developing country that needs a lot of funds to finance development. The need for additional capital budget from the private sector both from foreign and domestic investors. One of the policies that the Indonesian government needs to issue is a national strategic project. The birth of Law Number 11 of 2020 concerning Job Creation brings a new norm regarding the government's authority to intervene in regional taxes and fees in order to provide a good investment climate to attract investors to finance national strategic projects. The birth of this policy is considered contrary to the principle of regional autonomy. This paper examines the laws that allow government intervention in regional taxes related to the principle of regional autonomy. This study uses normative legal research methods. The results of the study show that the intervention of regional taxes and fees does not conflict with the principles of regional autonomy. Although the unitary state gives the widest possible authority to regional governments, the responsibility remains with the central government. In this paper, the ideal scheme of regional tax and user fees intervention is also explained by adding provisions for transfers from the central government to regional governments to increase regional revenues affected by the exemption and reduction of local tax and user fees. ___ Referensi Buku dengan penulis: Alboin Pasaribu dan Achmad Edi Subiyanto (ed.). (2018). Catatan Hukum Maria Farida Indrati, Jakarta: Konstitusi Press. Bagir Manan dan Kuntana Magnar. (1997). Beberapa Masalah Hukum Tata Negara Indonesia, Bandung: Alumni. Direktorat Jenderal Perimbangan Keuangan Kementerian Keuangan. (2021). Modul Penggalian Potensi Pajak Daerah dan Retribusi Daerah, Jakarta: Kementerian Keuangan. Erman Rajagukguk. (2019). Hukum Investasi Penanaman Modal Asing (PMA) dan Penanaman Modal Dalam Negeri (PMDN). Depok: Rajawali Pers. Indonesia, R. (1999). Undang-undang Nomor 22 Tahun 1999 tentang pemerintahan daerah. Jakarta: Bagian Proyek Peningkatan Publikasi Pemerintah, Direktorat Publikasi, Ditjen PPG, Deppen RI. Ismail, T. (2018). Potret Pajak Daerah di Indonesia. Jakarta: Kencana. Pudyatmoko, Y. (2006). Pengantar Hukum Pajak. Yogyakarta: Andi. Salim, H. S., & Sutrisno, B. (2008). Hukum Investasi di Indonesia. Depok: Rajawali Pers. Artikel jurnal: Adiyanta, F. S. (2019). Karakteristik Responsif Peraturan Daerah tentang Pajak-pajak Daerah sebagai Representasi dan Partisipasi Kehendak Publik. Administrative Law and Governance Journal, 2(3), 380-399. Azikin, A. (2018). Makna Otonomi Daerah Dalam Penyelenggaraan Pemerintahan Daerah Pada Era Reformasi. Jurnal Mp (Manajemen Pemerintahan), 35-41. Luthfy, R. M. (2019). Masa Jabatan Kepala Desa Dalam Perspektif Konstitusi. Masalah-Masalah Hukum, 48(4), 319-330. Sembiring, S. (2010). Hukum Investasi Pembahasan Dilengkapi dengan UU No. 25 Tahun 2007 tentang Penanaman Modal. Bandung: Nuansa Aulia. Sibuea, H. P. (2017). Rezim Otoriter dalam Bingkai Konstitusi Demokratis (Studi Tentang Rezim Otoriter di Indonesia dalam Bingkai Undang-Undang Dasar 1945 Sebagai Konstitusi Demokratis Berdasarkan Cita Hukum Pancasila). Jurnal IUS CONSTITUTUM, 1(1), 1-37. World Wide Web: Edi Suwiknyo. (2020). Mengintip Utak Atik Kebijakan Fiskal Daerah di UU Cipta Kerja, https://ekonomi.bisnis.com/read/20201015/9/1305324/mengintip-utak-atik-kebijakan-fiskal-daerah-di-uu-cipta-kerja . Diakses pada tanggal 25 November 2021. Henry D. Hutagaol. (2021). Hajat Hidup Orang Banyak dalam Kesemrawutan Regulasi Infrastruktur Pasif, https://www.kompas.id/baca/opini/2021/12/03/hajat-hidup-orang-banyak-dalam-kesemrawutan-regulasi-infrastruktur-pasif/ . Diakses pada tanggal 8 Oktober 2022. Henry D. Hutagaol. (2022). Internet Mahal, Tanggung Jawab Siapa. https://www.kompas.id/baca/artikel-opini/2022/02/09/internet-mahal-tanggung-jawab-siapa?utm_source=bebasakses_kompasid&utm_medium =whatsapp_shared&utm_content=sosmed&utm_campaign=sharinglink . Diakses pada tanggal 8 Oktober 2022. Kemenkominfo. (2018). Presiden: Proyek Strategis Nasional Harus Tekan Ketimpangan, https://kominfo.go.id/content/detail/12904/presiden-proyek-strategis-nasional-harus-tekan-ketimpangan/0/berita . Diakses pada tanggal 22 November 2021. KPPOD. (2016). Daerah Cenderung Andalkan Perda untuk Meningkatkan PAD. https://www.kppod.org/berita/view?id=504 . Diakses pada tanggal 8 Oktober 2022. Ramadhani Prihatini. (2017). Proyek Strategis Nasional Butuh biaya Rp 4197 T, https://nasional.kontan.co.id/news/proyek-strategis-nasional-butuh-biaya-rp-4197-t . Diakses pada tanggal 22 November 2021.